2022
DOI: 10.1002/cam4.4900
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory clinical trial of apatinib combined with intensity‐modulated radiation therapy for patients with unresectable hepatocellular carcinoma

Abstract: Purpose To evaluate the clinical efficacy and safety of apatinib combined with intensity‐modulated radiation therapy (IMRT) in patients with unresectable hepatocellular carcinoma (uHCC). Materials and methods Open‐label, single‐arm, exploratory clinical trial of apatinib combined with IMRT for uHCC patients. Patients aged 18–75 years with adequate hematological, liver, and renal functions and Eastern Cooperative Oncology Group (ECOG) performance status of ≤2 were enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Abulimiti et al (8) confirmed that IMRT plus sorafenib can improve the prognosis of advanced HCC, for which the mOS was observed to be 11.4 months and the mPFS was 6 months. Additionally, patients with advanced HCC who received IMRT in combination with apatinib had an mPFS of 7.8 months and an ORR of 15% (9). Radiotherapy can not only promote the generation and infiltration of T cells but also stimulate systemic anti-tumor immunity to control metastatic lesions, causing the "abscopal effect" (10).…”
Section: Introductionmentioning
confidence: 99%
“…Abulimiti et al (8) confirmed that IMRT plus sorafenib can improve the prognosis of advanced HCC, for which the mOS was observed to be 11.4 months and the mPFS was 6 months. Additionally, patients with advanced HCC who received IMRT in combination with apatinib had an mPFS of 7.8 months and an ORR of 15% (9). Radiotherapy can not only promote the generation and infiltration of T cells but also stimulate systemic anti-tumor immunity to control metastatic lesions, causing the "abscopal effect" (10).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, study [17] have pointed out that the mPFS of advanced HCC patients treated with IMRT combined with apatinib was 7.8 months and the ORR is 15%. All the studies mentioned above have indicated that radiotherapy had a synergistic effect on systemic antitumor therapy.…”
Section: Discussionmentioning
confidence: 99%
“…confirmed that radiotherapy combined with sorafenib improved the survival of patients with HCC, with a median OS of 11.4 months and a median PFS of 6 months ( 15 ). Furthermore, another study ( 16 ) indicated that the mPFS of patients with advanced HCC treated with IMRT combined with apatinib was 7.8 months and the ORR was 15%. All the studies mentioned above indicate that radiotherapy has a synergistic effect on systemic anti-tumour therapy.…”
Section: Discussionmentioning
confidence: 99%